(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
In the world, special importance is attached to the improvement of the technology for the development of individual-psychological and social activity of students of higher educational institutions, the creation of tools to support their initiative, and the introduction of effective pedagogical mechanisms based on cultural and communicative activities. This article discusses a number of specific aspects of the above task.